2022
DOI: 10.35848/1882-0786/ac9c46
|View full text |Cite
|
Sign up to set email alerts
|

Impact of undoped channel thickness and carbon concentration on AlN/GaN-on-SiC HEMT performances

Abstract: We report on a vertically scaled AlN/GaN HEMT technology design optimization for millimeter-wave applications. The undoped GaN channel thickness and carbon concentration into the buffer are extensively varied and systematically characterized. It is found that a thin GaN channel, typically below 150 nm improves the electron confinement, but increases the trapping effects, especially when using shorter gate lengths. Moreover, high carbon concentration into the buffer enables not only high electron confinement bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…The DIBL simulated is at per the experimental DIBL of the 0.4 μm gate length device. DIBL values of GaN HEMT are reported as 45mV V −1 for 90 nm gate length [47], 26mV V −1 100 nm gate length [48], 12 mV V −1 for 140nm gate length [49], 100 nm 40mV V −1 for 100 gate length [50]. Observing these results, it can be concluded that our device shows improvement after recess.…”
Section: Simulation Study To Suppress Scesmentioning
confidence: 51%
“…The DIBL simulated is at per the experimental DIBL of the 0.4 μm gate length device. DIBL values of GaN HEMT are reported as 45mV V −1 for 90 nm gate length [47], 26mV V −1 100 nm gate length [48], 12 mV V −1 for 140nm gate length [49], 100 nm 40mV V −1 for 100 gate length [50]. Observing these results, it can be concluded that our device shows improvement after recess.…”
Section: Simulation Study To Suppress Scesmentioning
confidence: 51%
“…One option consists in adopting a wider bandgap material for the top barrier layer, thus achieving a high 2DEG density even with a thin barrier thickness. To this aim, researchers have studied devices using thin AlN barriers [19], [20], [21], [40], InAl(Ga)N ternary and quaternary barriers [41], [42], [43], and ScAlN barriers [44], [45]; however, the study of the reliability of devices incorporating these new materials is still at its initial stage.…”
Section: Short-channel Effects In Gan Hemtsmentioning
confidence: 99%
“…SiC substrates. A total of four structures have been realized, consisting of an AlN nucleation layer and a 5 × 10 18 cm −3 carbon-doped GaN buffer allowing significantly reduced trapping effects when located away from the channel [ 33 ]. This is followed by a 100 nm AlGaN back barrier layer with an Al-content varying from 4% to 25% in order to evaluate the impact on the electron confinement.…”
Section: Device Technologymentioning
confidence: 99%
“…This requires extensive buffer engineering. Recently, we evaluated the impact of various carbon-doping concentrations into the buffer with different undoped GaN channel thickness on the device performance [ 33 ]. It was shown that a thin GaN channel, typically below 150 nm, combined with a high carbon concentration into the buffer leads not only to a high electron confinement under high drain bias for 100 nm GaN transistors, but also low leakage current at the expense of trapping effects.…”
Section: Introductionmentioning
confidence: 99%